Terms Expressing Social-Political Relationships in the “History of the Armenians” by Faustus of Byzantium - Abajyan, Anna; Yuzbashyan, Anahit (Bulletin of Yerevan University B: Philology, 2022)
Literary works written in Grabar// Old Armenian provide us with rich material about Grabar’s//Old Armenian’s term-system which needs to be analyzed wholly and comprehensively.In this work, the terms of Grabar// Old Armenian are examined based on the factual material ofthework"History of Hayq" by Pavstos Buzand. The vocabulary of the work and the term system which is its constituent part are multi-layered due to the content, purpose and various stylistic features of the work. The article examines the terms expressing socio-political-administrative political relations, which are multi-layered from the semantic point of view.The vocabulary of the work and the term system, making up its component, are multi-layered due to the content, purpose and various stylistic features of the work. The article examines terms expressing socio-administrative political relations, which are multi-layered from the semantic point of view. For the first time, the article presents the termswhich reflect: a) the country's hierarchy: the royal and military positions and the functions of officials, b) the state structure of the country with its infrastructures. Termsmanifesting conversion have been examined separately.Amongthe 50 presented terms, 13 terms are borrowed from Pahlavi, 6 from Greek, 31 are words from Armenian main word bank. In case of necessity, each term is also valued in diachronic perspective.The work is significantfrom the perspective of synchronicanalysis, but it also provides rich factual material for the historical//diachronic terminology, as most of the terms of theModern Eastern Armenian language have Grabarian//Old Armenianorigin.
Keywords: hierarchy of positions; political structure; administrative-political infrastructures; military and court positions; minister; patriarch; free; elder; consultant